Risk of mortality and suicide associated with substance use disorder among healthcare professionals: A systematic review and meta-analysis of observational studies - Rodrigues, Joao Vitor da Silva; Pereira, José E Guimarães; Passarelli, Luisa Almeida; Guatura, Gabrielle M G B; El Dib, Regina (Wolters Kluwer, 2021)
BACKGROUND: Previous studies have suggested that healthcare professionals may be susceptible to substance use disorders, and among the medical specialties, anaesthesia providers appear to be overrepresented. OBJECTIVE: We aimed to compare the prevalence of substance use-related mortality and suicides between anaesthesia and nonanaesthesia professionals. DESIGN: Systematic review of observational studies with meta-analyses. We defined anaesthesia providers as any healthcare professionals belonging to the specialty, regardless of age and duration of employment. Other healthcare professionals served as the control group. DATA SOURCES: Ovid Medline, EMBASE, Web of Science, Scopus, Scielo, LILACS and ProQuest databases up to March 2020. RESULTS: Thirty-nine studies were included, 31 cross-sectional studies involving 13 819 participants and eight cohorts with a total 129 811 participants proved eligible. Results suggested a higher rate of drug-related mortality with odds ratio (OR) 2.69 [95% confidence interval (CI), 1.80 to 4.00; P < 0.001; I2 = 0%, P = 0.55; high-certainty evidence] and suicide (OR 2.18, 95% CI, 1.33 to 3.58; P = 0.002; I2 = 0%, P = 0.68; moderate-certainty evidence) for anaesthesia providers compared with other healthcare professionals. CONCLUSION: High-to-moderate-certainty evidence shows that there is more than a two-fold increased rate of substance use-related mortality and suicide among anaesthesia providers compared with other healthcare professionals. Investigations examining substance abuse between healthcare professionals, with particular attention to working conditions and exposure are essential to further develop preventive strategies.